2013
DOI: 10.1016/j.meegid.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and molecular phylogeny of a newfound hantavirus harbored by the Doucet’s musk shrew (Crocidura douceti) in Guinea

Abstract: Elucidation of the molecular phylogeny of shrew-borne hantaviruses in sub-Saharan Africa has been hampered by the lack of full-length viral genomes. In this report, we present the complete genome analysis of a newfound hantavirus, designated Bowé virus, detected in ethanol-fixed intercostal muscle of a Doucet’s musk shrew (Crocidura douceti), captured in southwestern Guinea in February 2012. Full-length amino acid sequence comparison of the S-, M- and L-segment gene products revealed that Bowé virus differed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 26 publications
1
41
0
1
Order By: Relevance
“…That is, for nearly every new hantavirus, time-consuming and labor-intensive hit-and-miss efforts of designing and redesigning oligonucleotide primers were necessary. This brute-force approach was rewarded by the identification of genetically distinct hantaviruses (likely representing new viral species) in multiple species of shrews belonging to three subfamilies ( Soricinae , Crocidurinae and Myosoricinae ) and moles of two subfamilies ( Talpinae and Scalopinae ) captured in widely separated geographic regions (Arai et al, 2007, 2008a, 2008b, 2012; Gu et al, 2011, 2013a, 2013b, 2013c; Kang et al, 2009a, 2009b, 2009c, 2010c, 2011a, 2011b, 2011c; Song et al, 2007b, 2007c, 2009; Yashina et al, 2010). …”
Section: Hantavirus Huntingmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, for nearly every new hantavirus, time-consuming and labor-intensive hit-and-miss efforts of designing and redesigning oligonucleotide primers were necessary. This brute-force approach was rewarded by the identification of genetically distinct hantaviruses (likely representing new viral species) in multiple species of shrews belonging to three subfamilies ( Soricinae , Crocidurinae and Myosoricinae ) and moles of two subfamilies ( Talpinae and Scalopinae ) captured in widely separated geographic regions (Arai et al, 2007, 2008a, 2008b, 2012; Gu et al, 2011, 2013a, 2013b, 2013c; Kang et al, 2009a, 2009b, 2009c, 2010c, 2011a, 2011b, 2011c; Song et al, 2007b, 2007c, 2009; Yashina et al, 2010). …”
Section: Hantavirus Huntingmentioning
confidence: 99%
“…However, this self-imposed restriction reduced our virus-discovery opportunities, so we expanded the testing to include tissues preserved in RNAlater® RNA Stabilization Reagent with good success. More recently, because maintaining a cold chain under field conditions is not always feasible, we have found that archival tissues fixed in 90% ethanol are also suitable, as evidenced by the identification of a highly divergent hantavirus in ethanol-fixed liver tissue from banana pipistrelles ( Neoromicia nanus ) captured in Côte d’Ivoire (Sumibcay et al, 2012) and the full-length genome analysis of a hantavirus amplified from ethanol-fixed intercostal muscle of a Doucet’s musk shrew ( Crocidura douceti ) from Guinea (Gu et al, 2013c). Thus, ethanol-fixed tissues, originally collected for other purposes, should greatly expand the pool of specimens for hantavirus hunting, particularly tissues from other insectivorous small mammals, such as hedgehogs (order Erinaceomorpha) and tenrecs (order Afrosoricida).…”
Section: Hantavirus Huntingmentioning
confidence: 99%
“…The RdRp amino acid sequence similarity, which was highest (72.4% and 73.3%) between KMJV and ULUV (Table 1), exhibited six major conserved motifs (designated premotif A and motifs A, B, C, D, and E), like other hantaviruses (4,10).…”
mentioning
confidence: 99%
“…In analyzing RNA, extracted from more than 1,500 tissues from nearly 50 shrew species collected throughout Europe, Asia, North America, and Africa, between 1980 and 2012, we have discovered multiple genetically distinct hantaviruses, including Seewis virus (SWSV) in the Eurasian common shrew [ 83 -86 ], Ash River virus (ARRV) in the masked shrew ( Sorex cinereus ) [ 87 ], Jemez Springs virus (JMSV) in the dusky shrew ( Sorex monticolus ) [ 87 ], Kenkeme virus (KKMV) in the fl at-skulled shrew ( Sorex roboratus ) [ 88 ], Amga virus (MGAV) in the Laxmann's shrew ( Sorex caecutiens ) [ 89 ], Sarufutsu virus (SRFV) in the long-clawed shrew ( Sorex unguiculatus ) [ 90 ], Cao Bang virus (CBNV) in the Chinese mole shrew ( Anourosorex squamipes ) [ 91 ], Xinyi virus (XYIV) in the Taiwanese mole shrew ( Anourosorex yamanashi ) [ 92 ], Camp Ripley virus (RPLV) in the northern shorttailed shrew ( Blarina brevicauda ) [ 93 ], Iamonia virus (AMNV) in the southern short-tailed shrew ( Blarina carolinensis ) (unpublished), Boginia virus (BOGV) in the Eurasian water shrew [ 94 ], Azagny virus (AZGV) in the West African pygmy shrew ( Crocidura obscurior ) [ 95 ], Jeju virus (JJUV) in the Asian lesser whitetoothed shrew ( Crocidura shantungensis ) [ 96 ], Bowé virus (BOWV) in the Doucet's musk shrew ( Crocidura douceti ) [ 97 ], Uluguru virus (ULUV) in the geata mouse shrew ( Myosorex geata ) [ 98 ], and Kilimanjaro virus (KMJV) in the Kilimanjaro mouse shrew ( Myosorex zinki ) [ 98 ] (Table 9.2 ).…”
Section: Hantaviruses In Shrewsmentioning
confidence: 99%